2004
DOI: 10.1159/000072492
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Dilution vs. Post-Dilution during Continuous Veno-Venous Hemofiltration: Impact on Filter Life and Azotemic Control

Abstract: Background/Aims: To determine the impact of replacement fluid infusion site on filter life and azotemic control during continuous veno-venous hemofiltration (CVVH). Methods:Pre-dilution CVVH was conducted from February 2001 to December 2001 and then practice was changed to post-dilution (from January 2002 to July 2002). Filter life was prospectively observed and the following data obtained for each filter: starting date and time, ending date and time, heparin use, heparin dose and protamine use. Daily creatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 10 publications
1
61
1
1
Order By: Relevance
“…to create a fluid and blood separation. Administration of substitution fluids as 100% pre-filter has been associated with an increase in ‘filter life’ during CRRT [13]; however, data for bubble trap clotting with 100% post-dilution is not reported. It could be concluded that if pre-filter fluid administration reduces clotting within the membrane, fluids administration into the chamber (100% post-dilution) might reduce clotting in the chamber.…”
Section: Discussionmentioning
confidence: 99%
“…to create a fluid and blood separation. Administration of substitution fluids as 100% pre-filter has been associated with an increase in ‘filter life’ during CRRT [13]; however, data for bubble trap clotting with 100% post-dilution is not reported. It could be concluded that if pre-filter fluid administration reduces clotting within the membrane, fluids administration into the chamber (100% post-dilution) might reduce clotting in the chamber.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-dilution modality for HF has been shown to extend filter life on average by 5 h [10,11]. Thus, pre-dilution may be desirable in certain instances because of the decreased or even lack of need for anticoagulation [1], the advantages of which should include avoidance of the costs of administration and monitoring, as well as decreased risk of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…17 Depending on the therapy chosen, fluids in CRRT are administered into the blood before the hemofilter (predilution continuous venovenous hemofiltration) or after the hemofilter (postdilution continuous venovenous hemofiltration) or infused into the outside compartment of the hemofilter as a dialysate. Infusion of fluids before the filter can cause dilution of the blood and thus reduce the hematocrit of blood entering the hemofilter, leading to less hemoconcentration.…”
Section: Therapy Choice and Prevention Of Clottingmentioning
confidence: 99%
“…Infusion of fluids before the filter can cause dilution of the blood and thus reduce the hematocrit of blood entering the hemofilter, leading to less hemoconcentration. 4,17 Infusion of these same fluids after the filter has no effect on the blood entering the hemofilter. 17 Dialysate fluid used in continuous venovenous hemofiltration dialysis does not come in contact with the blood and therefore has no effect on the blood viscosity.…”
Section: Therapy Choice and Prevention Of Clottingmentioning
confidence: 99%
See 1 more Smart Citation